2022
DOI: 10.1002/jmv.27812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new “all in one” SARS‐CoV‐2 antigen‐detecting rapid diagnostic test and self‐test: Diagnostic performance and usability in child and adult populations

Abstract: The control of the COVID‐19 epidemics has been one global health priorities for the last two years. To that end, more reliable and easy‐to‐use, regardless of age, diagnostic tests are necessary. Considering that, we evaluated an innovative two‐step self‐test, the AAZ COVID‐VIRO ALL IN®, switching from the classic nasal swab to a nasal sponge. We performed a multicentre study, on 124 adults and children, in a point‐of‐care setting. Sensitivity, specificity and overall acceptance of the COVID‐VIRO ALL IN® self‐t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Among the 49 studies on nasal swabs containing 79,073 samples [ [2] , [3] , [4] , 6 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ], all of them were published between 2021 and 2022, and twenty-one studies were conducted in the USA [ 12 , 14 , 15 , 18 , 21 , 22 , [25] , [26] , [27] , [32] , [33] , [34] , [35] , 39 , 44 , 45 , [47] ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 49 studies on nasal swabs containing 79,073 samples [ [2] , [3] , [4] , 6 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ], all of them were published between 2021 and 2022, and twenty-one studies were conducted in the USA [ 12 , 14 , 15 , 18 , 21 , 22 , [25] , [26] , [27] , [32] , [33] , [34] , [35] , 39 , 44 , 45 , [47] ...…”
Section: Resultsmentioning
confidence: 99%
“…In addition to eliminating the drawbacks of nasopharyngeal swabs in terms of causing discomfort and possibly even damage to the patient [ 56 ], nasal swabs offered the option of home testing. Questionnaires were conducted in several studies, resulting that nearly all patients reported no pain in the anterior nasal collection, and it was easy to understand how to perform self-testing and interpret the test results [ 3 , 4 , 6 , 47 , 53 , 57 ]. Previous experience with HIV self-testing demonstrated that self-testers could perform HIV rapid diagnostic tests with reliability and accuracy [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a nasal sponge sampling for SARS‐CoV‐2 RAST showed a more comfortable experience in the child and adult populations. 28 Therefore, it is expected to increase the public's acceptance of SARS‐CoV‐2 RAST by using a new sampling approach in the future. Second, the economic level might play a considerable role in the intention to use SARS‐CoV‐2 RAST.…”
Section: Discussionmentioning
confidence: 99%